Proust, metodą Ollendorffa - Jan, Zieliński (Załącznik Kulturoznawczy, 2023)
The first part of the paper discusses the meandric cooperation between Marcel Proust and the Paris based publisher Paul Ollendorff that lasted over 20 years (1893-1913). Further on, the Western expansion of the Ollendorff family from Rawicz, Poland, is briefly sketched. Another passage concerns a Maeterlinck pastiche by Proust (Echo, 1911), seen in the context of Ollendorff’s conversation method of learning languages. The author suggests Proust was using this method to learn English himself. The paper ends with a survey of several mentions of Ollendorff’s method in the twentieth century Polish prose.